Analysis of Oxidative DNA Damage in HIV- Positive Pregnant Women - Rajekar, Rajesh Bhanudas; Kolgiri, Vaishali; Patil, Vinayak W. (International Journal of Innovative Research in Medical Science, 2017)
Objective: Oxidative stress is central to Human Immunodeficiency Virus (HIV) pathogenesis. Increased oxidative stress leads to increased oxidative DNA damage in HIV infected patients. The objective of this study was to analyse oxidative DNA damage in HIV- positive pregnant women. Methods: This was a case-control study involving 100 HIV-positive women as cases and 100 HIV-negative women as controls. We used plasma levels of the oxidized base, 8-hydroxy-2-deoxyguanosine (8-OHdG), as our biomarker of oxidative DNA damage. 8-OHdG was measured with the highly sensitive 8-OHdG check enzyme-linked immunosorbent assay (ELISA) kit. Results: Increased oxidative DNA damage was observed in HIV-positive pregnant women than HIV-positive non pregnant women and controls. Conclusion: Oxidative stress-induced DNA lesions may contribute to carcinogenesis. Hence management of oxidative stress induced DNA damage is very important in HIV-positive mothers and their newborns.